Effect of Ag loading on activated carbon doped ZnO for bisphenol A degradation under visible light - Khanitta Intarasuwan (2018)
© 2018 The Society of Powder Technology Japan Silver modified activated carbon doped zinc oxide (Ag/AC-ZnO) was synthesized via a calcination-electroless deposition route. The samples were characterized by X-ray powder diffractometry, scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, and UV–vis diffuse reflectance spectroscopy. The photocatalytic activity of the Ag/AC-ZnO was evaluated for bisphenol A degradation in the presence of H2O2under visible light irradiation. The archived results showed that the photocatalytic activity of the Ag/AC-ZnO was higher than that of AC-ZnO and pure ZnO. The cytotoxicity of the bisphenol A after photocatalysis under visible light irradiation was tested using L929 mouse fibroblast cells and the obtained results indicated that the treated bisphenol A solution exhibited no cytotoxicity against normal cells.